Pola Rekrutmen Politik Perempuan dalam Partai Politik: Studi Komparatif Partai Demokrat dan Partai Golkar - Kristina Kuryestra Halawa; Rizki Saiful Bahri; Ika Arinia Indryany (Journal of Legal, Political, and Humanistic Inquiry, 2026)
Women's political recruitment in Indonesian political parties reflects a complex interaction between institutional regulations, party organizational structures, and socio-cultural dynamics shaping women's political participation. This study examines the patterns of women's political recruitment through a comparative analysis of the Democratic Party and the Golkar Party. Using a qualitative approach based on document analysis and literature review, the study explores how internal party mechanisms, cadre development systems, and electoral dynamics influence the opportunities for female legislative candidates. The findings indicate that both parties formally support women’s participation through organizational structures, training programs, and the fulfillment of gender quota provisions mandated by national electoral regulations. However, the effectiveness of these commitments is constrained by internal party competition, the prioritization of candidate electability, and the persistence of male-dominated political networks. Within the open proportional electoral system, electoral success increasingly depends on candidates’ personal vote-mobilization capacity, which often places women at a structural disadvantage due to limited access to political resources and networks. Consequently, strengthening women's representation requires not only regulatory compliance but also institutional reforms, stronger cadre development for women, and more inclusive political practices within party organizations.